Peningkatan Kapabilitas PT. Nusantara Turbin dan Propulsi dalam Pemeliharaan Engine Makilla Series - Julianto, Ariek Valantino; Darmawan, Windi; Saleh, Ahmad Junaidi (Akademi Angkatan Udara, 2022)
This research is backgrounded by the difficulty of Indonesian Air Force in looking for domestic MROs and the defense industry in carrying out maintenance engine Makilla Series . This fact is a phenomenon “Capability of PT. Nusantara Turbin dan Propulsi Intermediaries in maintenance engine Makilla Series ”. So the problem was formulated how PT. Nusantara Turbin dan Propulsi capabilities were. PT. Nusantara Turbin dan Propulsi carries out repairs and maintenance engine Makilla Series . This research uses the theory of the defense industry, maintenance, defense industry models, human resources, capabilities, investment and financial performance. The research method used is qualitative descriptive and in analysis uses data reduction, data presentation and conclusion drawing. The results of this study formulate capabilities PT. Nusantara Turbin dan Propulsi Intermediaries in carrying out maintenance engine Makilla series based on the theory that has been taken. Suggestions for improving maintenance capabilities are PT. Nusantara Turbin dan Propulsi Intermediaries can innovate by empowering resources owned to manufacture local products against maintenance facilities with complexity and affordable technology so as to reduce investment costs. In addition, it is also recommended that the government's presence encourage investment in PT. Nusantara Turbin dan Propulsi for domestic market control especially TNI POLRI. Good collaboration between the Ministry of SOEs, BKPM (The Capital Planting Coordination Agency), the Ministry of Defense and the Ministry of Economy are expected to be realized so that the PT. Nusantara Turbin dan Propulsi can rise to reduce the dependence of weapon buying import. Improved HR quality did not escape the advice of the author.